"I'm Stuck": Women's Navigations of Social Networks and Prescription Drug Misuse in Central Appalachia. Issue 2 (October 2016) - Buer, Lesly‐Marie; Leukefeld, Carl G.; Havens, Jennifer R.
Abstract: This study utilizes anthropological analyses of kinship, care, gendered inequalities, and the state to examine how social networks affect women's substance use in a rural Appalachian county where the primary drug of choice is prescription opioids. Of 503 participants from a larger study of social networks among rural drug users, 16 women who reported using drugs with four or more other study participants (drug network members) were interviewed from November 2011 to February 2012. The purpose of interviews is to analyze the substance use patterns among participants who are highly connected in their networks. Female participants say they feel "stuck" in cycles of prescription drug misuse because of entrenchment in moral economies, intensive caretaking responsibilities, and violence from those in their networks. Although women demonstrate agency in their navigations of drug use, relationships, and economic and health inequalities, the factors that constrain women's actions culminate to create barriers for women accessing substance abuse treatment or decreasing substance use outside of treatment. This study adds to understandings of the relational and situational aspects of women's drug use and efforts to decrease use. Recognizing these aspects of women's lives will aid policies and programs in becoming more relevant to substance abusing women.